Laser forming of metal sheets - Wong, Zi Hao (2014)
This experiment is a study about laser forming, or more specifically laser bending of sheet metals. The materials used will be galvanised mild steel with a thickness of 0.5mm. Thermal gradient mechanism will be used when bending the specimens and data will be gathered to compare the relationship between bending angles and various other factors.